Sustainable last mile delivery network using social media data analytics - Ange-Marie Tuyishime; Omid Fatahi Valilai (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: The purpose of this research was to identify effective strategies to engage consumers to participate in the creation of a sustainable last-mile delivery network using social media and data analytics. Methodology: The research uses the data gathered through surveys to evaluate the customer motivation to contribute to the sustainability paradigm. Also, interaction models have been designed to elaborate the conceptual model and stakeholder interactions. Findings: Using social media as a tool, there would be a considerable potential to motivate the customers for contributing and enabling allowances for the last mile delivery problems. Customer engagement and communication will increase their role to achieve sustainable last-mile delivery. The application of autonomous methods of delivery should be considered to increase the awareness and trust of customers. Originality: This research is unique in terms of engaging the customers for sustainable last-mile delivery planning. Most of the sustainable last-mile delivery research focuses on business responsibility while also they are required for fulfilling the best service level for customers. Increasing awareness among customers can increase their participation for a trade-off in delivery service level while fulfilling sustainability.
urn:nbn:de:gbv:830-882.0200677; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Sustainability; Supply Chain Management; Logistics